TYPES OF LANGUAGE TEACHING METHODS AND ITS EFFICIENCY - Xidirova Halima Ulugʻbek's daughter (TADQIQOTLAR.UZ, 2024)
Abstract: In this article some information about language teaching methods has been provided .Also It has been illustrated that some samples and recommendations of the most effective language teaching methods and ways are presented.Effective methods are the key to effective understanding and explanation.